Exergy analysis and NOx emission of the H2-fueled micro burner with slinky projection shape channel for micro-thermophotovoltaic system. (19th March 2023) - He, Ziqiang; Kang, Dugang; Li, Xiuquan; Wang, Fei; You, Jingxiang; Xue, Zongguo; Zou, Qunfeng
Abstract: In order to improve the energy output of the MTPV system and reducing the NO x emission, a novel micro burner with a slinky projection shape channel for the MTPV system is proposed. To conduct the numerical simulation, 3-D models with detailed H2 /air reaction mechanisms and the extended Zeldovich mechanism of NO x generation are employed. The influence of the slinky projection amplitude, slinky projection fins number, and the basic oscillating channel radius on the energy conversion characteristics and the NO x emission is investigated. The increase of the slinky projection amplitude and slinky projection fins number can improve the energy output and exergy efficiency, as well as reduce the NO x emission. When the slinky projection amplitude is 0.4 mm and the slinky projection fins number is 42, the exergy efficiency reaches the maximum value of 70.3%, while the energy output of MTPV reaches the maximum value of 4.99 W at 10 m/s. Meanwhile, the decrease of the basic oscillating channel radius can significantly decrease the NO mole fraction at the outlet. Generally, an efficient technique to increase energy output and reduce NOx emission for the MTPV system is to introduce a micro burner with a slinky projection shape channel. Highlights: A novel slinky projection shape channel micro combustor for MTPV system is proposed. The influence of the slinky projection amplitude is studied. The influence of the slinky projection fins number is investigated. The influence of the basic oscillating channel radius is studied.